2009
DOI: 10.1016/j.jbiomech.2009.05.015
|View full text |Cite
|
Sign up to set email alerts
|

On the biomechanics of heart valve function

Abstract: Heart valves (HVs) are fluidic control components of the heart that ensure unidirectional blood flow during the cardiac cycle. However, this description does not adequately describe the biomechanical ramifications of their function in that their mechanics are multi-modal. Moreover, they must replicate their cyclic function over an entire lifetime, with an estimated total functional demand of least 3×10 9 cycles. The focus of the present review is on the functional biomechanics of heart valves. Thus, the focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
324
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(332 citation statements)
references
References 113 publications
(135 reference statements)
7
324
0
1
Order By: Relevance
“…Yet, we know that the MVAL undergoes very high strain rates during normal operation (29,62). However, it has been observed that valvular tissues are largely strain-rate insensitive (63), so that the responses measured here are likely to represent the in vivo response. The SHG imaging systems has been successfully utilized previously in several studies (7,64,65), although it does have resolution limitations and the results presented herein are necessarily limited by the technique's ability to distinguish fiber structures.…”
Section: Study Limitationsmentioning
confidence: 87%
“…Yet, we know that the MVAL undergoes very high strain rates during normal operation (29,62). However, it has been observed that valvular tissues are largely strain-rate insensitive (63), so that the responses measured here are likely to represent the in vivo response. The SHG imaging systems has been successfully utilized previously in several studies (7,64,65), although it does have resolution limitations and the results presented herein are necessarily limited by the technique's ability to distinguish fiber structures.…”
Section: Study Limitationsmentioning
confidence: 87%
“…Another limitation is that it only considered the singular effect of OSS on tissue formation which is thought to be beneficial [7,8,63]. It is however important to note that specimen movement may provide added benefits to tissue formation, by enhancing mass transport of nutrients to the growing tissues.…”
Section: Discussionmentioning
confidence: 99%
“…is suitable for scenarios with small displacement and conversely is not suitable for systems with massive boundary movement such as those that occur in valve leaflets (Kukreja et al, 2008;Oshima et al, 2001;Sacks et al, 2009b).…”
Section: Initial Algorithmic Methods Included the Eulerian And Lagranmentioning
confidence: 99%
“…elastic solid) (Nguyen and Lim, 2007), but it is not appropriate for systems with randomized boundary movement as it cannot treat arbitrary motion which can occur for example in heart valve disease states (e.g. severe mitral valve prolapse) (Oshima et al, 2001;Sacks et al, 2009b).…”
Section: Initial Algorithmic Methods Included the Eulerian And Lagranmentioning
confidence: 99%
See 1 more Smart Citation